Hubungan Work-Family Conflict dengan Subjective Well-Being Karyawan Bank BJB Divisi Kredit Konsumer - Almanda Nabila Rianda Putri; Sita Rositawati (Bandung Conference Series: Psychology Science, 2022)
Abstract. COVID-19 affects all sectors, including the banking sector. In responding to COVID-19, banks have made several new policies to stay afloat in the face of COVID-19 conditions. Bank Jawa Barat dan Banten (BJB) is the only Regional Development Banks (BPD) that can increase assets, profits and credit distribution. Moreover, Bank Jawa Barat dan Banten is dominated by female employees. In achieving goals, there is a conflict between roles at work and roles in the family. This conflict can lead to work-family conflict. The conflict can cause stress that will affect their psychological well-being. This study aims to examine the relationship between work-family conflict and subjective well-being of bank employees in Bank Jawa Barat and Banten (BJB) at Bandung. This study involved 161 female bank employees in Bank Jawa Barat dan Banten (BJB) in the consumer credit division who were married and had children at Bandung. The measuring instrument using the work-family conflict scale from Carlson, Kacmar, & William (2000), meanwhile the subjective well-being using the Scale of Positive and Negative Experience (SPANE) compiled by Ed Diener (2009) and The Satisfaction With Life Scale (SWLS) compiled by Diener, Emmons, Larsen & Griffin (1985). The method used the correlational with the calculation of the Pearson Rank correlation coefficient test. The results showed a correlation value of -0.632 which indicates that there is a negative correlation between work-family conflict and subjective well-being (affective component) and shows a correlation value of -0.362 which indicates that there is a negative correlation between work-family conflict and subjective well-being (cognitive component). Abstrak. COVID-19 berpengaruh pada segala sektor, termasuk sektor perbankan. Dalam menyikapi COVID-19, perbankan membuat beberapa kebijakan baru agar tetap bertahan dalam menghadapi kondisi COVID-19. Bank Jawa Barat dan Banten merupakan satu-satunya Bank Pembangunan Daerah (BPD) yang dapat meningkatkan aset, laba dan penyaluran kredit selain itu Bank Jawa Barat dan Banten didominisasi oleh karyawan perempuan. Dalam mencapai tuntutan tugasnya terdapat konflik antar peran, antara peran di pekerjaan dengan peran di keluarga. Konflik tersebut dapat mengakibatkan work-family conflict dan menimbulkan stres, stres yang dirasakan karyawan akan mempengaruhi kesejahteraan subjektifnya. Penelitian ini bertujuan untuk melihat hubungan work-family conflict dengan subjective well-being karyawan bank Jawa Barat dan Banten divisi kredit konsumer Kota Bandung. Penelitian ini melibatkan 161 karyawan perempuan bank Jawa Barat dan Banten divisi kredit konsumer Kota Bandung yang sudah menikah dan memiliki anak. Alat ukur yang digunakan yaitu work-family conflict scale dari Carlson, Kacmar, & William (2000) dan alat ukur subjective well-being dengan menggunakan Scale of Positive and Negative Experience (SPANE) yang di susun oleh Ed Diener (2009) dan The Satisfaction With Life Scale (SWLS) disusun oleh Diener, Emmons, Larsen & Griffin (1985). Metode yang digunakan yaitu korelasional dengan perhitungan statistik uji koefisien korelasi Rank Pearson. Hasil penelitian menunjukan nilai korelasi -0.632 yang menunjukan bahwa terdapat korelasi negatif antara work-family conflict dengan subjective well-being (komponen afektif) dan menunjukan nilai korelasi -0.362 yang menunjukan bahwa terdapat korelasi negatif antara work-family conflict dengan subjective well-being (komponen kognitif).